In Silico Study: the Potential of Apigenin Compounds from Moringa Plants as Inhibitors of Dihydroorotate Dehydrogenase Enzyme of Plasmodium Falciparum in Hepatic Malaria Therapy - Helena Elysia Argiyanti; I Dewa Made Widi Hersana; Risma Risma (Green Publisher Indonesia, 2026)
Malaria is a global health problem caused by Plasmodium infection, with hepatic malaria representing a serious complication due to liver dysfunction, particularly from Plasmodium falciparum. One promising therapeutic target is the enzyme dihydroorotate dehydrogenase (PfDHODH), which plays a crucial role in the parasite’s de novo pyrimidine synthesis. Moringa oleifera is known to contain various flavonoids with antimalarial and hepatoprotective activities, including apigenin. This study aimed to evaluate the potential of apigenin as an inhibitor of PfDHODH for hepatic malaria treatment using an in silico approach. The research employed a one-shot experimental design involving molecular docking simulations with AutoDock Vina, followed by pharmacokinetic, drug-likeness, and toxicity predictions using SwissADME, pkCSM, and ProTox3. Results showed that apigenin exhibited strong binding affinity to PfDHODH (-8.9 kcal/mol), comparable to the primary control ligand (-9.3 kcal/mol) and higher than artemisinin (-8.7 kcal/mol). Apigenin demonstrated favorable ADME properties, complied with Lipinski’s rule, and was classified as low toxicity (class 5) with no predicted carcinogenic effects. These findings indicate that apigenin from Moringa oleifera has promising potential as a PfDHODH inhibitor and may serve as a candidate for the treatment of hepatic malaria, warranting further experimental validation.